Efficacy and Safety of Direct-Acting Oral Anticoagulants (DOACs) in the Overweight and Obese - Kimberley Doucette; Hira Latif; Anusha Vakiti; Eshetu Tefera; Bhavisha Patel; Kelly Fitzpatrick (Advances in Hematology)
Obesity plays an essential role in the safety of pharmacologic drugs. There is paucity of data for direct oral anticoagulants (DOACs) in the obese, despite these agents becoming more widely used. The primary and secondary objectives of this study were to assess the safety and efficacy of DOACs in the overweight and obese populations when used for primary prophylaxis in the setting of non-valvular atrial fibrillation (NVAF) and for treatment of venous thromboembolisms (VTE). We conducted a retrospective cohort study in a large tertiary care center and obtained data through review of electronic health records. Among patients with NVAF and VTE on apixaban, there were no differences in rates of major bleeding (MB) and clinically relevant nonmajor bleeding (CRNMB) in the overweight and obese populations when compared to normal weight and underweight individuals. The multivariate adjusted analysis for rivaroxaban found that the odds of CRNMB for patients with BMI <25 was 5.37 (95% CI 1.50–19.32) times higher than that of BMI ≥25. Moreover, patients on medications that had known interactions with DOACs had 6.40 times higher odds of CRNMB than patients without such interactions (95% CI 1.49–27.57), which was not accounted for by the effects of aspirin and plavix alone. Efficacy was similar between all weight groups, for both apixaban and rivaroxaban. These results support previous analyses preformed in the large phase III trials and confirm that apixaban and rivaroxaban are safe in the overweight and obese.